Routine HIV testing in the emergency department: tough lessons in sustainability. (28th August 2013) - Rayment, M; Rae, C; Ghooloo, F; Doku, E; Hardie, J; Finlay, S; Gidwani, S; Atkins, M; Roberts, P; Sullivan, AK
Abstract : Objectives: Routine HIV testing in nonspecialist settings has been shown to be acceptable to patients and staff in pilot studies. The question of how to embed routine HIV testing, and make it sustainable, remains to be answered. Methods: We established a service of routine HIV testing in an emergency department (ED) in London, delivered by ED staff as part of routine clinical care. All patients aged 16 to 65 years were offered an HIV test (latterly the upper age limit was removed). Meetings were held weekly and two outcome measures examined: test offer rate (coverage) and test uptake. Sustainability methodology (process mapping; plan‐do‐study‐act (PDSA) cycles) was applied to maximize these outcome measures. Results: Over 30 months, 44 582 eligible patients attended the ED. The mean proportion offered an HIV test was 14%, varying from 6% to 54% per month over the testing period. The mean proportion accepting a test was 63% (range 33–100%). A total of 4327 HIV tests have been performed. Thirteen patients have been diagnosed with HIV infection (0.30%). PDSA cycles having the most positive and sustained effects on the outcome measures include the expansion to offer blood‐based HIV tests in addition to the original oral fluid tests, and the engagement of ED nursing staff in the programme. Conclusions: HIV testing can be delivered in the ED, but constant innovation and attention have been required to maintain it over 30 months. Patient uptake remains high, suggesting acceptability, but time will be required before true embedding in routine clinical practice is achieved.